Rino Levi e o estabelecimento da arquitetura moderna no Brasil - Alves, João Alex (2010)
Based on some of the different texts by the architect Rino Levi, in special: A arquitetura e a estética das cidades, São Paulo 1925 , O que há na arquitetura, 1939 , Acústica - Contribuição para a Solução do Problema da Acústica, 1936 , Mudam os Tempos, 1948 , Arquitetura é arte e ciência, 1949 , Síntese das Artes Plásticas, 1954 , Levantamento sobre as condições do ensino universitário da FAU-USP, 1956 , Evolução da arquitetura aula inaugural da Faculdade de Arquitetura da Universidade do Rio Grande do Sul, 1958 , Discurso de paraninfo da Faculdade de Arquitetura da Universidade do Rio Grande do Sul, 1958 , this research in History of Science shows aspects of his participation in the city of Sao Paulo development during the first half of the Twentieth Century, giving special attention to his ideas related to architecture as a field of knowledge. By exploiting certain points of the path taken by the architect since his formation and the publication of his first text to his professional practice already consolidated in the 50's and 60's in Sao Paulo this study emphasizes the contribution of Rino Levi for the institutionalization of architecture in Brazil. An attempt was made in this paper to relate social, cultural and economic aspects of that moment with information and ideas contained in Rino Levi s writings, as well as exposing how the architect has positioned itself in the face of the new architecture. The emergence of new materials made possible new ways and the industrialization brought with it various techniques for application in new construction, giving rise to modern architecture. Impacts of the actions of Rino Levi locally and internationally were also highlighted. By revisiting excerpts of the architect texts on the amendments by which passed the field of architecture we could see his thoughts on the development of new techniques and studies in architecture